2013
DOI: 10.3109/15622975.2013.866692
|View full text |Cite
|
Sign up to set email alerts
|

Use of electroconvulsive therapy in the Baltic states

Abstract: This 2010 survey revealed significant differences in the use and availability of ECT between the Baltic countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 21 publications
0
12
1
6
Order By: Relevance
“…Regional variation within countries has been attributed to service factors or barriers to access as well as regional treatment traditions. 13 , 14 , 17 19 Different regional treatment traditions might also influence the within-country availability of ECT in Sweden, as might the regional differences of availability of anesthesiologists and psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…Regional variation within countries has been attributed to service factors or barriers to access as well as regional treatment traditions. 13 , 14 , 17 19 Different regional treatment traditions might also influence the within-country availability of ECT in Sweden, as might the regional differences of availability of anesthesiologists and psychiatrists.…”
Section: Discussionmentioning
confidence: 99%
“…Unilateral position as a second option is mentioned only in Estonia and Ukraine (Lõokene et al 2014, Olekseev et al 2014). …”
Section: Discussionmentioning
confidence: 99%
“…However, heterogeneity in ECT delivery, both nationally and internationally, is a concern. A comprehensive contemporary review of worldwide ECT practice and variability demonstrated substantial heterogeneity [2] with high variability in the United States [3][4][5], Canada [6,7], Australia [8], the Netherlands [9], Belgium [10], Central and Eastern Europe [11], Greece [12], Spain [13], the Baltic States [14], Saudi Arabia [15], South Africa [16], Nigeria [17], Russia [18], Thailand [19], Japan, [20], India [21] and other Asian countries [22,23].…”
Section: Introductionmentioning
confidence: 99%